RNA-seq and metabolomic analyses of beneficial plant phenol biochemical pathways in red alder - Hixson, Kim K.; Meng, Qingyan; Moinuddin, Syed G. A.; Kwon, Mi; Costa, Michael A.; Cort, John R.; Davin, Laurence B.; Bell, Callum J.; Lewis, Norman G. (Frontiers in Plant Science, 2024)
Red alder (Alnus rubra) has highly desirable wood, dye pigment, and (traditional) medicinal properties which have been capitalized on for thousands of years, including by Pacific West Coast Native Americans. A rapidly growing tree species native to North American western coastal and riparian regions, it undergoes symbiosis with actinobacterium Frankia via their nitrogen-fixing root nodules. Red alder's desirable properties are, however, largely attributed to its bioactive plant phenol metabolites, including for plant defense, for its attractive wood and bark coloration, and various beneficial medicinal properties. Integrated transcriptome and metabolome data analyses were carried out using buds, leaves, stems, roots, and root nodules from greenhouse grown red alder saplings with samples collected during different time-points (Spring, Summer, and Fall) of the growing season. Pollen and catkins collected were collected from field grown mature trees. Overall plant phenol biochemical pathways operative in red alder were determined, with a particular emphasis on potentially identifying candidates for the long unknown gateway entry points to the proanthocyanidin (PA) and ellagitannin metabolic classes, as well as in gaining better understanding of the biochemical basis of diarylheptanoid formation, i.e., that help define red alder's varied medicinal uses, and its extensive wood and dye usage.